Determinants of persistence of symptoms and impact on physical and mental wellbeing in Long COVID: A prospective cohort study. Issue 4 (April 2022) - Righi, Elda; Mirandola, Massimo; Mazzaferri, Fulvia; Dossi, Giuditta; Razzaboni, Elisa; Zaffagnini, Amina; Ivaldi, Federico; Visentin, Alessandro; Lambertenghi, Lorenza; Arena, Cinzia; Micheletto, Claudio; Gibellini, Davide; et al.
Highlights: Advanced age, ICU admission and multiple symptoms at onset are predictors of Long COVID among patients with SARS-CoV-2 infection. Female gender and persistence of symptoms at day 28 and month 9 were risk factors for psychological distress. Prolonged symptoms have negative impact on both physical and mental wellbeing. Studies on Long COVID determinants and consequences are encouraged to identify target populations for recovery interventions. Summary: Background: Residual symptoms can be detected for several months after COVID-19. To better understand the predictors and impact of symptom persistence we analyzed a prospective cohort of COVID-19 patients. Methods: Patients were followed for 9 months after COVID-19 onset. Duration and predictors of persistence of symptoms, physical health and psychological distress were assessed. Results: 465 patients (54% males, 51% hospitalized) were included; 37% presented with at least 4 symptoms and 42% complained of symptom lasting more than 28 days. At month 9, 20% of patients were still symptomatic, showing mainly fatigue (11%) and breathlessness (8%). Hospitalization and ICU stay vs. non-hospitalized status increased the median duration of fatigue of 8 weeks. Age > 50 years (OR 2.50), ICU stay (OR 2.35), and presentation with 4 or more symptoms (OR 2.04) were independent predictors of persistence of symptoms at month 9. A total of 18% of patients did not return to optimal pre-COVID physical health, while 19% showed psychological distress at month 9. Hospital admission (OR 2.28) and persistence of symptoms at day 28 (OR 2.21) and month 9 (OR 5.16) were independent predictors of suboptimal physical health, while female gender (OR 5.27) and persistence of symptoms at day 28 (OR 2.42) and month 9 (OR 2.48) were risk factors for psychological distress. Conclusions: Patients with advanced age, ICU stay and multiple symptoms at onset were more likely to suffer from long-term symptoms, which had a negative impact on both physical and mental wellbeing. This study contributes to identify the target populations and Long COVID consequences for planning long-term recovery interventions.